Evaluation of the Effectiveness of Mammography in Early Detection of Breast Cancer and the Impact of Regular Screening Programs in Iraqi Women - Raad Abdalrahman Hameed (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Breast cancer is the most common malignancy among women globally, including in Iraq, where late diagnosis often leads to poor outcomes. Early detection through mammography has proven to reduce mortality by identifying cancer at more treatable stages. Aims and Objectives: The primary objective of this research is to determine the effectiveness of mammography in detecting breast cancer at early stages and to assess the role of regular screening programs in improving diagnosis and survival outcomes among Iraqi women. By identifying patterns and challenges in screening participation, this study aims to provide evidence-based recommendations for improving breast cancer prevention efforts in Iraq. Methodology: A sample of 1,500 women aged 40 years and older was recruited from various healthcare centers across Iraq. The study employed a cross-sectional design, collecting data through mammograms, follow-up diagnostic procedures, and patient questionnaires to assess screening frequency and medical history. Results: Among the participants 1500 women, 270 women (18%) had abnormal mammography results, with follow-up biopsies confirming malignancies in 165 cases (11%). Notably, 137 of these confirmed cases (83%) were diagnosed at stage I or II, demonstrating the advantage of early screening. In contrast, women with irregular or no screening history were more likely to be diagnosed at advanced stages (III or IV). Regular screening participants—those receiving mammograms annually or biennially-accounted for 74% of the early-stage detections, highlighting the positive impact of consistent screening.These findings align with broader research indicating that the positive predictive value (PPV) of screening increases with age and family history of breast cancer, as seen in similar studies that found higher PPVs among older women and those with a family historyThe results indicate that mammography is highly effective in identifying breast cancer at an early stage, significantly improving prognosis and survival rates. However, barriers such as cultural stigma, limited access to healthcare, and low awareness levels reduce screening participation. The study recommends expanding nationwide screening programs, promoting regular mammography, and addressing barriers to access. Conclusion, Mammography is a vital tool in lowering breast cancer mortality in Iraq, and normal screening plays a essential function in early detection, improving remedy consequences, and saving lives.